Variant U1 snRNAs are implicated in human pluripotent stem cell maintenance and neuromuscular disease. Issue 22 (17th August 2016) - Vazquez-Arango, Pilar; Vowles, Jane; Browne, Cathy; Hartfield, Elizabeth; Fernandes, Hugo J. R.; Mandefro, Berhan; Sareen, Dhruv; James, William; Wade-Martins, Richard; Cowley, Sally A.; Murphy, Shona; O'Reilly, Dawn
Abstract: The U1 small nuclear (sn)RNA (U1) is a multifunctional ncRNA, known for its pivotal role in pre-mRNA splicing and regulation of RNA 3΄ end processing events. We recently demonstrated that a new class of human U1-like snRNAs, the variant (v)U1 snRNAs (vU1s), also participate in pre-mRNA processing events. In this study, we show that several human vU1 genes are specifically upregulated in stem cells and participate in the regulation of cell fate decisions. Significantly, ectopic expression of vU1 genes in human skin fibroblasts leads to increases in levels of key pluripotent stem cell mRNA markers, including NANOG and SOX2. These results reveal an important role for vU1s in the control of key regulatory networks orchestrating the transitions between stem cell maintenance and differentiation. Moreover, vU1 expression varies inversely with U1 expression during differentiation and cell re-programming and this pattern of expression is specifically de-regulated in iPSC-derived motor neurons from Spinal Muscular Atrophy (SMA) type 1 patient's. Accordingly, we suggest that an imbalance in the vU1/U1 ratio, rather than an overall reduction in Uridyl-rich (U)-snRNAs, may contribute to the specific neuromuscular disease phenotype associated with SMA.